CONTENT OF THE CONCEPT «SCIENTIFIC AND PEDAGOGICAL ACTIVITY» IN THE FRAMEWORK OF MODERN EDUCATIONAL PARADIGM - Iryna V. Tamozhska (Alfred Nobel University Publisher, 2021)
The author examines the definitions used in legislative documents and pedagogical research connected with the activity of subjects - participants of the educational process («scientific and pedagogical activity», «scientific activity», «pedagogical activity», «creative pedagogical activity», «professional pedagogical activity»). It is stated that the generic concept of the term «scientific and pedagogical activity» («scientific activity», «pedagogical activity») is defined depending on who is the subject of such an activity (a scientist or an educator). The conclusion is drawn that such categories as «scientific activity» and «pedagogical activity» are not identical. The domestic experience related to the interpretation of the concept «pedagogical activity» was analysed. The researchers considered it to be a special kind of social activity, a kind of socially useful activity implemented by adults, teachers' activity in the course of educational process, a creative process of conscious, purposeful, self-regulated activity of the teacher. It is stressed that the methodological subsystem is indirectly present in such subsystems of teachers' creative pedagogical activity as didactic, educational, organizational and administrative, social-pedagogical and self-improvement ones. The levels of teachers' creative pedagogical activities (reproductive, labour-saving, design, innovative ones) were specified. The article is focused on the content of the concept «function of the professional activities of academic staff», which is treated as an invariant component of productive activity of academic staff, the effectiveness of which is provided by applied educational tools, taking into account modern tendencies and developmental peculiarities of education institutions, as well as the level of their professional ability. The main types of teachers' professional and pedagogical activities are determined (diagnostics of professional orientation, ability to learn, teach and educate; design activity; learner-centred professional training; social and professional education; extracurricular educational work; raising the level of professional and pedagogical education and qualification; innovative activity). The organizational and pedagogical conditions for structuring scientific and pedagogical activities of academic staff in higher education institutions were generalized (ensuring structural and functional unity; staff and structural units' optimization; standardization of information links; ensuring multifaceted development of academic staff and their self-organization; compliance with the principles of systematicity and complexity in the implementation of professional and job functions). The functions of professional activity of academic staff were distinguished (administrative, motivational, developmental, prognostic, corrective, culturological, educational, professional, the function of providing educational services).